DO CEO CHARACTERISTICS AND MANAGEMENT REAL INFLUENCE PROFITS COMPANY PERFORMANCE? EVIDENCE FROM INDONESIA - Safitri, Rika Henda; Wijaya, Ferencia Maria; Yuniartie, Emylia; Kalsum, Umi (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2024)
This study addresses a significant research gap in the transportation and logistics sector, focusing on the impact of CEO characteristics and Real Earnings Management (REM) on firm performance. Given the sector's critical role in the global economy and its substantial changes pre- and post-COVID-19, this research is particularly relevant. Using multiple regression analysis (MRA), the study examines CEO Narcissism, Education Level, Gender, and Tenure in IDX-listed firms from 2018 to 2022. Results indicate that CEO Narcissism and Education Level do not significantly affect performance, while Gender has a positive impact, and Tenure negatively influences performance. Additionally, there is no significant link between Narcissism/Education and REM practices, but REM moderates the relationships between Gender, Tenure, and firm performance. These findings provide valuable insights for stakeholders, highlighting the importance of managing earnings effectively to boost financial performance, investor confidence, and sustainable growth in the transportation and logistics sector.